Self-powered active antibacterial clothing through hybrid effects of nanowire-enhanced electric field electroporation and controllable hydrogen peroxide generation. (November 2018) - Chiu, Che-Min; Ke, Yi-Yun; Chou, Ting-Mao; Lin, Yu-Jhen; Yang, Po-Kang; Wu, Chih-Cheng; Lin, Zong-Hong
Abstract: Pathogenic bacteria that give rise to infection have posed major health concerns over the past several decades. In this paper, we propose a self-powered active disinfection system controlled by human motions. The system is mainly composed of a multilayered triboelectric nanogenerator (m-TENG) for the harvesting of biomechanical energy and conductive fabrics as electrodes for the wearable disinfection system. The working principle of the system is based on hybrid effects of H2 O2 production and electroporation, which provide good disinfection performance toward gram-negative Escherichia coli ( E. coli ) and gram-positive Staphylococcus aureus ( S. aureus ). In addition, we also demonstrate that the presence of gold-coated tellurium nanowires (Au-Te NWs) on the fabrics increased the strength of local electric field and enhanced the system's disinfection performance. With the help of Au-Te NWs, the disinfection activities of the system reach values of more than 87% and 96% against S. aureus and E. coli, respectively, when the m-TENG was operated at a frequency of 1 Hz for 60 min. Furthermore, the disinfection activity can be strengthened by increasing the operation frequency or electric output of the m-TENG. Alternatively, the generated electricity can be stored in a capacitor to achieve rapid disinfection via an instantaneous discharging process. Because of the fiber-based structure in the disinfection device and the shoe-embedded design of the m-TENG, our proposed self-powered active disinfection system can be easily integrated into commercial textiles to fabricate smart clothes to combat pathogenic bacteria. Graphical abstract: The concept of self-powered active disinfection system for clothing is proposed. A m-TENG is embedded in shoe soles to harvest mechanical energy from human motions. CFFs modified with Au-Te nanowires function as electrodes of the disinfection device. The electric output from the m-TENG enables simultaneous disinfection of bacteria inside the CFFs through the hybrid effects of H2 O2 production and electroporation. fx1 Highlights: Carbon fiber fabrics modified with Au-Te nanowires were fabricated. The hybrid effects of hydrogen peroxide generation and electroporation were realized for sterilization. The concept of the self-powered antibacterial system is potential to develop smart clothes.